Method for evaluating adhesion effect of asphalt thermal recycling agent on recycled asphalt and aggregate

Through an evaluation method of asphalt heat regenerator on the adhesion of regenerated asphalt and aggregates, the problem of poor water stability and insufficient adhesion in the humid, hot and rainy areas in the southern part of the south is solved, and more efficient road durability is achieved.

CN119804306APending Publication Date: 2025-04-11GUANGDONG JIAOKE TECH R & D CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411765046.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the thermal regeneration technology of asphalt pavement has poor water stability in humid, hot and rainy areas in the south, resulting in water damage such as pits and grooves within 3-5 years, seriously affecting the durability of the pavement, and the regenerator fails to effectively improve the adhesion between aging asphalt and aggregates.

Method used

A method for evaluating the adhesion of bitumen and aggregates with thermal regenerator is provided. By calculating and recording the asphalt peeling on aggregates, the improvement index ΔT is calculated to evaluate the adhesion of thermal regenerator on regenerated bitumen and aggregates.

Benefits of technology

This method can more accurately evaluate the adhesion effect between different aggregates and aged asphalt, and select regenerators suitable for humid, hot and rainy areas in the south, so as to improve the durability of thermally regenerated asphalt pavement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for evaluating the adhesion effect of an asphalt thermal recycling agent on recycled asphalt and aggregate, which comprises the following steps: respectively and effectively wrapping the aggregate and aged asphalt, and binding with an iron wire to prepare an aged sample wrapped with the asphalt; the aggregate and the recycled asphalt are effectively wrapped and bound with an iron wire, and a recycled sample wrapped with the asphalt is prepared; respectively putting the aged sample and the regenerated sample into boiling water for heating, and recording the asphalt peeling condition on the aggregate in the test process; and calculating to obtain an improvement index for evaluating the improvement performance of the thermal recycling agent on the adhesion of the recycled asphalt and the aggregate according to the spalling condition of the asphalt on the aggregate. Compared with a traditional grading evaluation method, the method has the advantages that evaluation can be carried out more accurately, and the adhesiveness effects between different aggregates and aged asphalt can be effectively distinguished; meanwhile, the method can also be used for evaluating the improvement effect of the regenerant on the aged asphalt, and the proper regenerant can be conveniently screened; meanwhile, the adhesiveness effect between the aggregate and the recycled asphalt can be detected, and whether the aggregate meets the construction requirement or not is detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road engineering, and in particular to a method for evaluating the effect of an asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate. Background Art

[0002] my country already has the longest expressway mileage in the world, and its transportation infrastructure is huge. However, as the roads built earlier are now entering a period of large-scale maintenance, how to maintain and preserve these huge infrastructures is a difficult problem that needs to be solved urgently.

[0003] Asphalt pavement is one of the main pavement structures of my country's highways. Asphalt pavement thermal regeneration technology is one of the effective ways to recycle aged asphalt mixtures, and has been promoted on a large scale in the highway field in recent years.

[0004] However, during the large-scale promotion process, it was found that the water stability of hot regeneration of asphalt pavement was poor. After 3-5 years of using hot regeneration asphalt pavement in the hot and rainy southern regions, water damage such as potholes appeared, which seriously affected the durability of the pavement and restricted the promotion of hot regeneration technology of asphalt pavement. Further research found that one of the important reasons was that the regeneration agent failed to effectively improve the adhesion between the aged asphalt and the aggregate.

[0005] At present, the Technical Specification for Highway Asphalt Pavement Regeneration JTG / T 5521-2019 only limits the regeneration agent based on physical indicators such as density and mass loss. This indicator cannot specifically screen out regeneration agents suitable for the hot and humid rainy areas in the south. There are a lot of regeneration agents on the market. The reason is that there is a lack of evaluation methods for the adhesion between regeneration agents and recycled asphalt and aggregates. Therefore, it is urgent to invent a method for evaluating the adhesion between regeneration agents and recycled asphalt and aggregates, so as to specifically screen out regeneration agents suitable for the hot and humid rainy areas in the south and improve the durability of hot recycled asphalt pavements. Summary of the invention

[0006] In view of the above problems, the present invention aims to provide a method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate, which is easy to analyze and calculate.

[0007] To achieve the technical purpose, the scheme of the present invention is: a method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate, and the specific steps are as follows:

[0008] S1. Calculate and weigh a specified amount of regeneration agent, and mix the regeneration agent with aged asphalt to obtain regenerated asphalt;

[0009] S2. Effectively wrapping the aggregate with aged asphalt and tying them with iron wire to obtain aged samples wrapped with aged asphalt; effectively wrapping the aggregate with recycled asphalt and tying them with iron wire to obtain recycled samples wrapped with recycled asphalt;

[0010] S3. Under standard atmospheric pressure, the aged samples and the regenerated samples were placed in boiling water for heating respectively, and the asphalt peeling on the aggregate was recorded during the test. The time when the asphalt began to peel off was t0, the time when half of the asphalt was peeled off was t1, and the time when the asphalt was completely peeled off was t2;

[0011] S4. The improvement index ΔT used to evaluate the improvement performance of the thermal regeneration agent on the adhesion between the regenerated asphalt and the aggregate is obtained by calculating the asphalt peeling condition on the aggregate.

[0012] Preferably, in step S1, the amount of the regeneration agent is determined according to the test methods in Appendix D and Appendix E of the Technical Specifications for Highway Asphalt Pavement Regeneration JTG / T5521-2019.

[0013] Preferably, in step S2, the aggregate is effectively coated with recycled asphalt and aged asphalt according to the test method of T0616 of "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011); the number of aged samples is greater than or equal to three, and the number of recycled samples is greater than or equal to three.

[0014] Preferably, in step S4, the adhesion index T between asphalt and aggregate is first calculated as: T=k1*t0+k2*t1+k3*t2; wherein k1 is the weight coefficient of the time when asphalt starts to peel off, k2 is the weight coefficient of the time when half of the asphalt area is peeled off, and k3 is the weight coefficient of the time when asphalt is completely peeled off;

[0015] The improvement index ΔT of the regeneration agent on the adhesion between asphalt and aggregate is:

[0016] ΔT=T1-T2=k1*(t 10 -t 20 )+k2*(t 11 -t 21 )+k3*(t 12 -t 22 );

[0017] T1 is the recycled asphalt adhesion index between recycled asphalt and aggregate; t 10 is the time when asphalt in the regenerated sample starts to peel off; t 11 is the time for half the asphalt area in the regenerated sample to peel off; t 12 is the time for the asphalt in the recycled sample to completely peel off; T2 is the adhesion index of the aged asphalt to the aggregate; T 20 is the time when asphalt starts to peel off in the aged sample; t 21 is the time for half the asphalt area in the aged sample to peel off; t 22 It is the time when the asphalt in the aged sample is completely peeled off.

[0018] Preferably, when t0 is less than or equal to 20 s, t1-t0 is less than 5 s, or t2-t1 is less than 5 s, it means that the sample is unqualified and the data is not used.

[0019] Preferably, the aggregate is one of granite, diabase, metamorphic sandstone, limestone or basalt.

[0020] Preferably, the regeneration agent is a petroleum-based regeneration agent.

[0021] Preferably, if T1 is less than 900s, the aged asphalt has been severely aged and does not meet the requirements for the use of thermal regeneration technology.

[0022] The beneficial effect of the present invention is that compared with the traditional grading evaluation method, the present application can perform evaluation more accurately and can effectively distinguish the adhesion effects between different aggregates and aged asphalt; at the same time, the method of the present application can also be used to evaluate the improvement effect of the regeneration agent on aged asphalt, which is convenient for screening suitable regeneration agents; at the same time, it can also detect the adhesion effect between aggregates and regenerated asphalt to detect whether it meets the construction requirements. DETAILED DESCRIPTION

[0023] The present invention is further described in detail below with reference to specific embodiments.

[0024] The specific embodiment of the present invention is a method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate, and the specific steps are as follows:

[0025] Step 1: Determine the amount of regeneration agent according to the test methods in Appendix D and Appendix E of the Technical Specification for Highway Asphalt Pavement Regeneration JTG / T 5521-2019; mix the regeneration agent with the aged asphalt to obtain the regenerated asphalt. The regeneration agent is preferably a bio-oil regeneration agent or an extracted oil regeneration agent from a petroleum-based regeneration agent.

[0026] Step 2: According to the test method of "Testing Procedures for Asphalt and Asphalt Mixtures for Highway Engineering" (JTG E20-2011) T0616, the aggregate is effectively coated with asphalt, and the aggregate is effectively coated with aged asphalt and tied with iron wire to obtain aged samples coated with asphalt; the aggregate is effectively coated with recycled asphalt and tied with iron wire to obtain recycled samples coated with asphalt;

[0027] Step 3: Under standard atmospheric pressure, the aged sample and the regenerated sample coated with asphalt are placed in boiling water respectively, and the aggregate coated with asphalt is heated in boiling water;

[0028] Step 4: During the test, the asphalt peeling conditions on the aggregates were recorded respectively. The time when the asphalt peeling on the aggregates began was t0, the time when half of the asphalt on the aggregates (i.e. the peeling area was greater than or equal to half of the total area of ​​the aggregates) was peeled off was t1, and the time when the asphalt on the aggregates was completely peeled off was t2.

[0029] To avoid partial sample production failure and large-scale local shedding; when t0 is less than or equal to 20s, t1-t0 is less than 5s, or t2-t1 is less than 5s, it means that the sample production failure is unqualified and the data will not be used.

[0030] Step 5: The improvement index ΔT used to evaluate the performance of the thermal regeneration agent in improving the adhesion between the recycled asphalt and the aggregate is obtained by calculating the asphalt peeling condition on the aggregate.

[0031] First, calculate the adhesion index T between asphalt and aggregate: T = k1*t0+k2*t1+k3*t2; (1)

[0032] Among them, k1 is the weight coefficient of the time when asphalt starts to peel off, k2 is the weight coefficient of the time when half of the asphalt area is peeled off, and k3 is the weight coefficient of the time when asphalt is completely peeled off. The value range of k1 in the weight coefficient is 0.4-0.6, and the value range of k2 and k3 is 0.1-0.3; when the aggregate is granite, basalt, or diabase, k1=0.5, k2=0.25, and k3=0.25 are preferred. When the aggregate is metamorphic sandstone or limestone, k1=0.6, k2=0.2, and k3=0.2 are preferred.

[0033] According to formula (1), the adhesion index T1 of recycled asphalt to aggregate can be obtained as follows:

[0034] T1=k1*t 10 +k2*t 11 +k3*t 12 ; (2)

[0035] Where: t 10 is the time when asphalt in the regenerated sample starts to peel off; t 11 is the time for half the asphalt area in the regenerated sample to peel off; t 12 It is the time for the asphalt in the reclaimed sample to be completely stripped off;

[0036] According to formula (1), the adhesion index T2 of aged asphalt to aggregate can be obtained as follows:

[0037] T2=k1*t 20 +k2*t 21 +k3*t 22 ; (3)

[0038] Where: T 20 is the time when asphalt starts to peel off in the aged sample; t21 is the time for half the asphalt area in the aged sample to peel off; t 22 It is the time when the asphalt in the aged sample is completely peeled off.

[0039] The improvement index ΔT of the adhesion between asphalt and aggregate obtained by the regeneration agent is calculated by formula (2) and (3):

[0040] ΔT=T1-T2= k1*t 10 +k2*t 11 +k3*t 12 -k1*t 20 -k2*t 21 -k3*t 22 ; (4)

[0041] The improvement index of J type regeneration agent is: ΔT j =T j1 -T j2 ; (5)

[0042] The best regeneration agent is selected according to the test results. Under the same material and aggregate conditions, ΔT j The larger the value, the better the improvement effect of the J type regeneration agent. j1 The larger the value, the better the adhesion between the recycled asphalt prepared by J type regeneration agent and the aggregate.

[0043] Embodiment 1

[0044] This method is used to evaluate the adhesion effect of aged asphalt with granite and diabase aggregates. If the traditional method is used, the adhesion between granite and aggregate can only be graded manually according to the adhesion between aged asphalt and granite aggregate, which is defined as 1-5 according to the grading method. However, when the adhesion between asphalt and aggregate is the same grade defined by the traditional method, the adhesion effect between asphalt and aggregate is still different. The traditional method can only be used as a qualitative evaluation method. This method is a quantitative evaluation method, which can quantitatively determine the adhesion effect between different aged asphalt and aggregate.

[0045] As shown in Table 1. According to the traditional method, the adhesion between the aged asphalt and the granite aggregate is level 5, and the adhesion between the aged asphalt and the diabase aggregate is level 5. However, according to this method, the adhesion index T2 of the aged asphalt between the aged asphalt and the granite aggregate can be quantitatively determined to be 735s, and the adhesion index T2 of the aged asphalt between the aged asphalt and the diabase aggregate can be quantitatively determined to be 1423.7s, which shows that the adhesion effect of the aged asphalt and the diabase is better.

[0046] Table 1: Comparison of adhesion effects between different aggregates and aged asphalt

[0047]

[0048]

[0049] Embodiment 2

[0050] This method can be used to determine the type of regeneration agent based on the evaluation of the effect of the regeneration agent on the adhesion between aged asphalt and diabase aggregate. According to the above method, the regeneration agent is screened, and after adding the regeneration agent to the aged asphalt, the test is conducted again to determine the improvement effect of the regeneration agent. The results are shown in Table 2 below. It can be seen that a non-petroleum-based regeneration agent has a better improvement index on the adhesion between aged asphalt and aggregate, so a non-petroleum-based regeneration agent should be selected to improve the water damage resistance of the regenerated asphalt.

[0051] Table 2: Comparison of improvement indicators of different rejuvenators on aged asphalt

[0052] Regeneration Agent Effect of regeneration agent on improving adhesion between asphalt and aggregate ΔT A petroleum-based regeneration agent 95s A non-petroleum-based regeneration agent 185s

[0053] Embodiment 3

[0054] This method can be used to evaluate the adhesion effect of aged asphalt and granite aggregate and determine its renewability. According to the above method, pressed oil bio-oil regeneration agent A (classified as RA-1 according to the Technical Specification for Regeneration of Highway Asphalt Pavement (JTG / T 5521-2019)) was added to the aged asphalt, and the test was conducted again to determine the water damage resistance of the aged asphalt and the recycled asphalt. The results are shown in Table 3 below.

[0055] Table 3: Comparison of adhesion effects between different aggregates and recycled asphalt

[0056]

[0057] It can be seen that the adhesion between aged asphalt, recycled asphalt and granite aggregate is poor. After adding the regeneration agent, the improvement effect of the regeneration agent on the adhesion between asphalt and aggregate is ΔT=36s. It can be seen that the improvement effect of the regeneration agent on the adhesion between the aged asphalt and the aggregate is poor. At the same time, the adhesion effect T1 of the recycled asphalt and aggregate is 773.8s, which does not meet the requirement that the adhesion effect between asphalt and aggregate should be ≥900s, indicating that the aged asphalt has been severely aged and cannot be treated by thermal regeneration technology.

[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any slight modification, equivalent substitution and improvement made to the above embodiment based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. A method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate, characterized in that: The specific steps are as follows: S1. Calculate and weigh a specified amount of regeneration agent, and mix the regeneration agent with aged asphalt to obtain regenerated asphalt; S2. Effectively wrapping the aggregate with aged asphalt and tying them with iron wire to obtain aged samples wrapped with aged asphalt; effectively wrapping the aggregate with recycled asphalt and tying them with iron wire to obtain recycled samples wrapped with recycled asphalt; S3. Under standard atmospheric pressure, the aged samples and the regenerated samples were placed in boiling water for heating respectively, and the asphalt peeling on the aggregate was recorded during the test. The time when the asphalt began to peel off was t0, the time when half of the asphalt was peeled off was t1, and the time when the asphalt was completely peeled off was t2; S4. The improvement index ΔT used to evaluate the improvement performance of the thermal regeneration agent on the adhesion between the regenerated asphalt and the aggregate is obtained by calculating the asphalt peeling condition on the aggregate.

2. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 1, characterized in that: In step S1, the amount of regeneration agent is determined according to the test methods in Appendix D and Appendix E of the Technical Specifications for Highway Asphalt Pavement Regeneration JTG / T5521-2019.

3. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 1, characterized in that: In step S2, the aggregate is effectively coated with recycled asphalt and aged asphalt according to the test method of "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011) T0616; the number of aged samples is greater than or equal to three, and the number of recycled samples is greater than or equal to three.

4. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 3, characterized in that: In step S4, the adhesion index T between asphalt and aggregate is first calculated as: T = k1*t0+k2*t1+k3*t2; wherein k1 is the weight coefficient of the time when asphalt starts to peel off, k2 is the weight coefficient of the time when half of the asphalt area is peeled off, and k3 is the weight coefficient of the time when asphalt is completely peeled off; The improvement index ΔT of the regeneration agent on the adhesion between asphalt and aggregate is: ΔT=T1-T2=k1*(t 10 -t 20 )+k2*(t 11 -t 21 )+k3*(t 12 -t 22 ); T1 is the recycled asphalt adhesion index between recycled asphalt and aggregate; t 10 is the time when asphalt in the regenerated sample starts to peel off; t 11 is the time for half the asphalt area in the regenerated sample to peel off; t 12 is the time for the asphalt in the recycled sample to completely peel off; T2 is the adhesion index of the aged asphalt to the aggregate; T 20 is the time when asphalt starts to peel off in the aged sample; t 21 is the time for half the asphalt area in the aged sample to peel off; t 22 It is the time when the asphalt in the aged sample is completely peeled off.

5. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 4, characterized in that: When t0 is less than or equal to 20s, t1-t0 is less than 5s, or t2-t1 is less than 5s, it means that the sample is unqualified and the data is not used.

6. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 1, characterized in that: The aggregate is one of granite, diabase, metamorphic sandstone, limestone or basalt.

7. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 1, characterized in that: The regeneration agent used in step S1 is a petroleum-based regeneration agent.

8. The method for evaluating the effect of asphalt thermal regeneration agent on the adhesion between regenerated asphalt and aggregate according to claim 4, characterized in that: If T1 is less than 900s, the aged asphalt has been severely aged and does not meet the requirements for the use of thermal regeneration technology.